Palm Tocotrienol Activates the Wnt3a/β-Catenin Signaling Pathway, Protecting MC3T3-E1 Osteoblasts from Cellular Damage Caused by Dexamethasone and Promoting Bone Formation - Norfarahin Abdullah Sani; Nur Aqilah Kamaruddin; Ima Nirwana Soelaiman; Kok-Lun Pang; Kok-Yong Chin; Elvy Suhana Mohd Ramli (Biomedicines)
Background and aim: Prolonged glucocorticoid (GC) treatment increases oxidative stress, triggers apoptosis of osteoblasts, and contributes to osteoporosis. Tocotrienol, as an antioxidant, could protect the osteoblasts and preserve bone quality under glucocorticoid treatment. From this study, we aimed to determine the effects of tocotrienol on MC3T3-E1 murine pre-osteoblastic cells treated with GC. Methods: MC3T3-E1 cells were exposed to dexamethasone (150 µM), with or without palm tocotrienol (PTT; 0.25, 0.5, and 1 µg/mL). Cell viability was measured by the MTS assay. Alizarin Red staining was performed to detect calcium deposits. Cellular alkaline phosphatase activity was measured to evaluate osteogenic activity. The expression of osteoblastic differentiation markers was measured by an enzyme-linked immunoassay. Results: Enhanced matrix mineralization was observed in the cells treated with 0.5 µg/mL PTT, especially on day 18 (p < 0.05). The expression of Wnt3a, β-catenin, collagen 1α1, alkaline phosphatase, osteocalcin, low-density lipoprotein receptor-related protein 6, and runt-related transcription factor-2 were significantly increased in the PTT-treated groups compared to the vehicle control group, especially at 0.5 µg/mL of PTT (p < 0.05) and on day 6 of treatment. Conclusions: PTT maintains the osteogenic activity of the dexamethasone-treated osteoblasts by promoting their differentiation.